Pengembangan Sistem Pemesanan Tiket Bus Online Berbasis Web dan Mobile Pada PO. Logos: Development of an Online Bus Ticket Reservation System Based on Web and Mobile for PO. Logos - Nuswantoro, Setio Ardy; Sutami, Sutami; Prasetya, Pahdian Bagus (Jurnal Sains Komputer dan Teknologi Informasi, 2025)
The development of information and computer technology has simplified various aspects of life, including transportation, particularly in the area of bus ticket reservations. The manual ticket reservation system still in use has several drawbacks, such as low efficiency, the risk of running out of tickets, and data entry errors. This study aims to design and develop a web and mobile-based bus ticket reservation information system for PT. Po. Logos. By using the waterfall method, this system is expected to improve operational efficiency and customer service. The system developed utilizes PHP programming language and MySQL database to manage ticket data, schedules, and reservations in real-time. Through user-friendly interface design and secure transaction processes, the system aims to address the issues present in the manual reservation system. This research also contributes to the advancement of technology in the transportation sector and opens up further opportunities for innovation in digital-based transportation services.